PERANCANGAN KARYA VISUAL DALAM KONTEKS IMPLEMENTASI SENI GRAFITI PADA PRODUK BONGGOL JAGUNG “MATAHATI”: DESIGNING VISUAL WORK IN THE CONTEXT OF IMPLEMENTING GRAFFITI ART ON CORNCOB PRODUCTS “MATAHATI” - MT Ardynata; Cama Juli Rianingrum; Ahadiat Joedawinata (Universitas Trisakti, 2025)
Designing Visual Work In The Context Of Implementing Graffiti Art On Corncob Products “Matahati”. The rapid development of graffiti art in Indonesia has expanded its application to various media and products. This study aims to design visual works by implementing graffiti art on corncob-based products developed by Matahati. The research focuses on how graffiti art enhances the visual appeal of products targeted at young audiences and children, creating new market segments and increasing sales. A qualitative approach was employed, with the design process consisting of five stages: orientation, analysis, concept, design, and implementation. Data validation was conducted through triangulation using observation, interviews, and questionnaires. The results demonstrate that applying graffiti art to Matahati corncob products successfully introduced visual innovation, enriching the aesthetic appeal and attracting new market segments. This creative touch not only increases product uniqueness but also boosts sales, particularly among those valuing aesthetics and creativity. The study significantly contributes to the creative industry by integrating agricultural waste into innovative product designs, supporting sustainability while enhancing aesthetic value. Overall, the research highlights opportunities for the creative industry to produce products that are both artistic and sustainable.